2021
DOI: 10.1159/000516693
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Dependent Enhancement and the Critical Pattern of COVID-19: Possibilities and Considerations

Abstract: Coronavirus disease 2019 (COVID-19), a pandemic infection with profound effects on human society, has been emerged recently and rigorously challenged our ability to control viral infections. Although at the beginning of the COVID-19 outbreak, the epidemic seems controllable in Southern Iran, the disease presents a critical pattern as of May 2020. After a few months of COVID-19 emergence, in a twisted turn of events, the severity and mortality of COVID-19 increased dramatically. It has been proposed that the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 65 publications
0
5
0
1
Order By: Relevance
“…One of the oldest polyclonal approaches dating back to the late nineteenth century, known as hyperimmune equine serum therapy, has also been used in efforts to treat COVID-19. For this approach, IgG from horses immunized with SARS-CoV-2 spike protein were collected, proteolytically cleaved to F(Ab′) 2 fragments to reduce immunogenicity as well as to minimize potential adverse effects (such as antibody dependent enhancement, or ADE [ 196 ] (see also Sect. 4.3.2 ), and used to treat COVID-19 patients [ 5 – 7 ].…”
Section: Convalescent Patient and Polyclonal Therapeutic Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the oldest polyclonal approaches dating back to the late nineteenth century, known as hyperimmune equine serum therapy, has also been used in efforts to treat COVID-19. For this approach, IgG from horses immunized with SARS-CoV-2 spike protein were collected, proteolytically cleaved to F(Ab′) 2 fragments to reduce immunogenicity as well as to minimize potential adverse effects (such as antibody dependent enhancement, or ADE [ 196 ] (see also Sect. 4.3.2 ), and used to treat COVID-19 patients [ 5 – 7 ].…”
Section: Convalescent Patient and Polyclonal Therapeutic Approachesmentioning
confidence: 99%
“…Both antibodies possess the “TM” triple mutations L234F/L235E/P331S described by Oganesyan et al [ 420 ] to decrease their binding to human FcγRI, FcγRIIa, FcγRIIIa, and C1q, resulting in reduced ADCC, ADCP, and complement-dependent cytotoxicity (CDC). These mutations also reduce the theoretical risk of ADE [ 196 ]. Additionally, both antibodies have the M252Y/S254T/T256E “YTE” modification [ 421 ] in their Fc to extend their half-life in circulation (called “LAAB, long-acting antibody”).…”
Section: Descriptions Of Key Antibodies Targeting Sars-cov-2mentioning
confidence: 99%
“…When SARS-CoV-2 enters human cells, its spike protein plays a critical role by binding to angiotensin-converting enzyme 2 (ACE2) on host cells [ 43 ]. The SARS-CoV-2 spike protein is composed of two subunits S1 and S2; S1 contains a receptor-binding domain, which recognizes and binds to ACE2 [ 44 ]. Molecular docking analysis indicated that eugenol interacts with the SARS-CoV-2 spike protein as a possible ligand [ 45 ].…”
Section: Anti-covid-19 Activity Of Eugenolmentioning
confidence: 99%
“…However, the emergence of highly contagious variants continues to diminish the efficacy and utility of the available vaccines and antibody-based treatments against these new variants. Additionally, the phenomenon of antibody-dependent enhancement (ADE), defined by the possible post-infection or post-vaccination entry of immune complexes into cells with Fc receptors, as observed previously during pre-clinical studies of SARS-CoV and MERS-CoV vaccine development, has been a significant concern for the advancement of COVID-19 vaccines [31,32]. Since the onset of the pandemic, the approaches to diagnosing, treating, and vaccinating against COVID-19 have continually evolved, driven by the emergence of novel virus variants worldwide, and antibodies targeting SARS-CoV-2 have been instrumental in shaping these strategies.…”
Section: Introductionmentioning
confidence: 99%